Mechanisms and genetics of neurodevelopmental cognitive disorders - Smith, Moyra (Academic Press, 2021)
Mechanisms and Genetics of Neurodevelopmental Cognitive Disorders connects neurodevelopment with genetics and behavior to better understand the underlying factors leading to cognitive neurodevelopmental disorders. This book focuses on mechanisms of disease and follows the development of specific brain regions, functions, and gene expression to causes and processes in autism, attention deficit disorder, and learning disabilities. Topics include brain mapping, brain plasticity, epigenetics, neuroimmunology, and many other factors that influence the development of these diseases. This book will promote understanding of recent investigations and developments related to brain development from fetal life onward with specific relevance to neurodevelopmental cognitive disorders and conditions. This is an essential reference for anyone who is looking to learn more about different aspects of neurodevelopment and emerging concepts in psychiatric disorders.